2010
DOI: 10.1007/s00705-010-0763-4
|View full text |Cite
|
Sign up to set email alerts
|

Two novel mastreviruses from chickpea (Cicer arietinum) in Australia

Abstract: Two novel mastreviruses (genus Mastrevirus; family Geminiviridae), with proposed names chickpea chlorosis virus (CpCV) and chickpea redleaf virus, are described from chickpea (Cicer arietinum) from eastern Australia. The viruses have genomes of 2,582 and 2,605 nucleotides, respectively, and share similar features and organisation with typical dicot-infecting mastreviruses. Two distinct strains of CpCV were suggested by phylogenetic analysis. Additionally, a partial mastrevirus Rep sequence from turnip weed (Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Although a number of different viruses cause disease in these crops, in some areas at least, mastreviruses are believed to be the main biotic constraint to chickpea production [31]. Despite their importance, only recently has the characterisation of these viruses been undertaken, with the identification of two potentially new mastrevirus species in Sudan and Pakistan ( [9]; B. Gronenborn, unpublished) and three potentially new species identified in Australia [14]. In view of the vast geographical range where CSD is reported, it would seem likely that further mastrevirus diversity is probably present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of different viruses cause disease in these crops, in some areas at least, mastreviruses are believed to be the main biotic constraint to chickpea production [31]. Despite their importance, only recently has the characterisation of these viruses been undertaken, with the identification of two potentially new mastrevirus species in Sudan and Pakistan ( [9]; B. Gronenborn, unpublished) and three potentially new species identified in Australia [14]. In view of the vast geographical range where CSD is reported, it would seem likely that further mastrevirus diversity is probably present.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this BeYDV had only been identified affecting beans in South Africa [10,11]. In Australia, the country where the first dicot-infecting mastrevirus (TbYDV) was identified [12], a CSD-like disease of chickpea has recently been shown to be caused by three distinct viruses, referred to as Chickpea chlorosis virus-A (CpCV-A), Chickpea chlorosis virus-B (CpCV-B) and Chickpea red leaf virus (CpRLV) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the huge effect of CSD and their wide distribution, very few species has been identified like in Sudan and Pakistan [24], and another three identified in possibly new species Australia [41]. Also the CpCDV from Syria has been directly identified after these new species [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, O. orientalis Matsumura has also been reported to transmit CpCDV to plant species of different families (like Fabaceae, Solanaceae, Chenopodiaceae) and induced CpCDV like symptoms (Horn et al, 1996;Kumari et al, 2004;Farzadfar et al, 2008;Akhtar et al, 2011). Nonetheless, Horn et al (1993) reported first time the identification of CpCDV along with many reports from other countries like, Australia, Africa, Europe, the Middle East, Asia, and Far East, Arabian Peninsula and the Indian subcontinent (Horn et al, 1993;Makkouk et al, 1995Makkouk et al, , 1998El-Muadhidi et al, 2001;Farzadfar et al, 2002;Makkouk et al, 2003a,b;Kumari et al, 2004;Nahid et al, 2008;Thomas et al, 2010;Muhire et al, 2013;Akhtar et al, 2014).…”
Section: Mastrevirus Vector -Orosius Albicinctus Distantmentioning
confidence: 99%
“…Albeit Bean yellow dwarf virus (BeYDV) (Liu et al, 1997a) (infect dicotyledonous plants) presence has been recorded in both Pakistan and South Africa (Halley-Scott et al, 2007). However, Thomas et al (2010) reported Chickpea chlorosis virus (CpCV-A, CpCV-B) and Chickpea redleaf virus (CpRLV) from Australia. Previously, CpCDV has been noted down to attack the legumes but with lapse of time, they expand their host range and infected other dicot families as well, like pepper (in India and Oman) and tomato (Byun et al, 2014;Akhtar et al, 2014;Zia et al, 2015).…”
Section: Turnip Curly Topmentioning
confidence: 99%